Corporate Governance Quality and Capital Structure Dynamics: Evidence from Pakistan - Khan, Muhammad Imran; Saba, Irum; Kouser, Rehana (Indonesian Journal of Sustainability Accounting and Management, 2022)
Corporate governance is highlighted as an important aspect of developing economies. The literature well explained the relationship between corporate governance and capital structure, but little is known about the role of debt as a takeover defense and disciplinary tool, particularly for a debt-based economy such as Pakistan. This study used data from 173 non-financial firms listed on a stock exchange in Pakistan from 2008 to 2017. For the empirical investigation, the study incorporated the Orthogonal Generalized Method of Momentum approach to unbalanced panel data owing to endogeneity. The findings show that in over-levered firms, the adjustment speed of capital structure is slower with weak corporate governance. This result indicates that managers use debt as a takeover defense tool to protect their jobs, even at the cost of shareholders’ benefits. However, for under-levered firms, the adjustment speed of capital structure with weak governance is slower. This aspect specifies that the disciplinary effect of debt is more important for managers. This study concludes that managers with weak corporate governance take benefits at the cost of shareholders’ wealth. The study recommends that managers should develop an understanding of corporate governance to safeguard the rights of the shareholders.